Effects of fly ash on mechanical and physical properties of earth-based construction. (30th December 2017) - Ma, Cong; Xie, Youjun; Long, Guangcheng; Chen, Bing; Chen, Longzhu
Highlights: The influence of fly ash on the mechanical and physical properties of earth-based construction is investigated. The relationships of mechanical and physical properties to curing time are analyzed by hyperbolic models. The controlling parameters of the hyperbolic models can be calculated by CSCN and fly ash contents. Abstract: The earth-based construction with unique advantages of wide raw material origin, energy conservation and environment protection has attracted growing attention recently. Although the mechanical properties can be improved by adding a high-efficiency stabilizer named as CSCN, it is difficult to generalize the application of CSCN due to the relatively high cost of several chemical admixtures. In this study, fly ash is introduced, and its influences on mechanical and physical properties of earth-based construction are investigated. Judged from laboratory results, mechanical properties including compressive strength and secant modulus increase as stabilizer contents and curing time increase. Water content of stabilized earth decreases due to more significant cement hydration and pozzolanic reactions by adding more stabilizer. Additionally, unit weight increases slightly with the increase of stabilizer content and curing time. The relationships of mechanical and physical properties to curing time have been estimated by hyperbolic models, and the calculation formulae for strength, modulus and physical indexes are developed. The controlling parameters of the hyperbolic models have been expressed through CSCN and FA contents by percent based on exponential regression analysis. The precision of calculation formulae is confirmed through comparing calculated values with experimental results, and the deviation is mostly lower than 10%. These results can guide the design of earth-based construction and help engineers keep track of changes in physical properties with service time.